PEMILIHAN KATA DALAM RUBRIK URLAUBS-/FREIZEITBEKANNTSCHAFTEN SURAT KABAR ONLINE SÜDDEUTSCHE ZEITUNG - Parnaningroem, Raden Roro Dyah Woroharsi; Wahyuningsih, Fahmi; Pujosusanto, Ari (Universitas Negeri Surabaya, 2022)
One of the abilities of living beings is to interact with each other. The medium used is language. By using language, one can get to know others through digital programs. Süddeutsche Zeitung, an online newspaper in Germany provides an introduction room that is Heirats- & Bekanntschaftsanzeigen (wedding advertisements and introductions) which has five rubrics. One of the rubrics is Urlaubs-/Freizeitbekanntschaften. This qualitative descriptive research seeks to analyze the nouns and adjectives selected by the authors of the advertisement in the rubric Urlaubs-/Freizeitbekanntschaften. (Introduction to find people who are willing to accompany in vacation time or leisure time). This kind of rubric is interesting, because it does not yet exist in Indonesia. With the language research method, 15 data from Süddeutsche Zeitung online August 6, 2022, August 13, 2022, and August 20, 2022 were analyzed. The results showed that 50% of work/status nominas were used by ad authors to introduce themselves and more than 75% of ad authors used adjektives that were affixed to nomina in a position as sentence objects in order to get the desired acquaintance. Key Words: Word choice, Urlaubs-/Freizeitbekanntschaften, newspaper